Kehamilan Dengan Gagal Ginjal Kronis - Nastiti Hemas Mayangsari (Jurnal Ilmu Kedokteran, 2023)
Pregnancy is a condition of multisystemic changes in a woman's body to adapt to the presence of the fetus. Physiological changes also occur in the kidneys and urinary tract and persist until the postpartum period. Chronic Kidney Disease (CKD) is a condition of kidney damage in which the estimated glomerular filtration rate (eGFR) is less than 60 mL/min for three months. In general, CKD occurs in 10-14% of the population. About 1 in 750 pregnant women has chronic kidney failure grades 3-5. Despite its low incidence, CKD in pregnancy can cause severe Fetomaternal complications.